Green Building Implementation Study Based on Eficiency Energi in Ru-mah Joglo as Development of Teaching Materials Course Program and Planning Application - Andini Dwi P; A.G. Thamrin; Chundakus Habsya (Universitas Sebelas Maret, 2020)
This research was purposed to knowing (1) the implementation of green building on aspect natural lighting in Rumah Joglo terms of SNI 03-6197-2000; (2) the implementation of green building on aspect natural ventilation in Rumah Joglo terms SNI 03-6572-2001; (3) the implementation of green building in Rumah Joglo for development of teaching materials course Program and Planning Application in PTB FKIP UNS. This research was conducted by measuring the natural lighting, air velocity, relative huminidity, and air temperature in each room in the Rumah Joglo as well as the occupants questionnaire provide. The subjects were five Rumah Joglo. The result showed that 89,74% of natural lighting in the research subjects does not meet the requirements of SNI 03-6197-2000, 82,25% of air velocity does not meet the requirements of SNI 03-6572-2001, for relative huminidity and air temperature in the object of study does not meet the requirements of SNI 03-6572-2001.